Probability, stochastic processes, and queueing theory : the mathematics of computer performance modelling - Nelson, Randolph (Springer-Verlag, 1995)
This textbook provides a comprehensive introduction to probability and stochastic processes, and shows how these subjects may be applied in computer performance modeling. The author's aim is to derive probability theory in a way that highlights the complementary nature of its formal, intuitive, and applicative aspects while illustrating how the theory is applied in a variety of settings.